Co-digestion of microalgae with potato processing waste and glycerol: effect of glycerol addition on methane production and the microbial community. Issue 61 (9th October 2020) - Zhang, Yanghanzi; Caldwell, Gary S.; Blythe, Philip T.; Zealand, Andrew M.; Li, Shuo; Edwards, Simon; Xing, Jin; Goodman, Paul; Whitworth, Paul; Sallis, Paul J.
Abstract : Glycerol as an additional co-substrate enhanced methane yields by up to 128% when co-digestion with microalgae and potato waste. Abstract : The production of methane-rich biogas from the anaerobic digestion (AD) of microalgae is limited by an unfavorable biomass carbon-to-nitrogen (C/N) ratio; however, this may be ameliorated using a co-digestion strategy with carbon-rich feedstocks. For reliable plant operation, and to improve the economics of the process, secure co-feedstock supply (ideally as a waste-stream) is important. To this end, this study investigated the feasibility of co-digesting microalgae ( Chlorella vulgaris ) with potato processing waste (potato discarded parts, PPWdp ; potato peel, PPWp ) and glycerol, while monitoring the response of the methanogenic community. In this semi-continuous study, glycerol (1 and 2% v/v) added to mixtures of C. vulgaris : PPWdp enhanced the specific methane yields the most, by 53–128%, whilst co-digestion with mixtures of C. vulgaris : PPWp enhanced the methane yields by 62–74%. The microbial communities diverged markedly over operational time, and to a lesser extent in response to glycerol addition. The acetoclast Methanosaeta was abundant in all treatments but was replaced by Methanosarcina in the potato peel with glycerol treatment due to volatile fatty acid (VFA) accumulation. Our findings demonstrate that the performance of microalgae co-digestion is substantially improved by the addition of glycerol as an additional co-feedstock. This should improve the economic case for anaerobically digesting microalgae as part of wastewater treatment processes and/or the terminal step of a microalgae biorefinery.